Case Report: A case of persistent fifth aortic arch associated with stenosis and interrupted aortic arch - Yi, Gao; Zehang, Hu; Shumin, Fan (Frontiers in Pediatrics, 2025)
Persistent fifth aortic arch (PFAA) is a rare congenital cardiovascular anomaly, often associated with other defects such as interrupted aortic arch (IAA) or patent ductus arteriosus (PDA). We report a 12-day-old male neonate presenting with respiratory distress, edema, and oliguria. Physical examination revealed a grade 2/6 systolic murmur at the left sternal border. Echocardiography identified PFAA with coarctation, IAA, PDA, and an atrial septal defect (ASD), confirmed by cardiac CT. Surgical intervention included aortic arch repair, fifth arch excision, and ASD closure. The postoperative recovery was smooth, and the patient remained clinically well with normal cardiac function during the 1-year follow-up period. This case underscores the critical role of echocardiography in early diagnosis and surgical planning for complex congenital heart disease.